PELAKSANAAN SISTEM PEMBINAAN NARAPIDANA DI LEMBAGA PEMASYARAKATAN (STUDI KASUS PADA LEMBAGA PEMASYARAKATAN KLAS IIB MUARA SIJUNJUNG) - Lukman firnando putra; Alchonity Harika Fitri (Jurnal Restorative Justice, 2020)
The penitentiary system has an important role in guiding prisoners, so guiding prisoners have several components that work interrelated to achieve a goal. This system, known as the penitentiary system, has an important role in guiding prisoners as a crime prevention effort, because the prisoners have various problems that should receive attention in the form of assistance so that they obtain motivation to live in the future and be able to adjust to the new environment and not become a residif. The purpose of this study is to find out the guidance system, constraints and efforts made by Class IIB Correctional Institution staff in Muara Sijunjung in overcoming problems that arise in the formation of prisoners. The author uses sociological juridical research using primary data obtained through interviews with 2 officials or employees in agencies, and in the form of criminal statistics in the Class IIB Penitentiary Muara Sijunjung and documents. The results of the data analysis are efforts to overcome the problems that arise in the formation of prisoners in the Class IIB Correctional Facility Muara Sijunjung: Over capacity, the government has given remissions which directly can reduce the density of prisoners in Correctional Institutions, Budget, the government seeks to utilize available funds effective and efficient to achieve optimal results in fostering prisoners, human resources, the government should collaborate with other institutions, such as universities that have good religious instruction.